Carpal Tunnel Syndrome: Primary Care and Occupational Factors - Saint-Lary, Olivier; Rébois, Arnaud; Mediouni, Zakia; Descatha, Alexis (Frontiers in Medicine, 2015)
Carpal tunnel syndrome (CTS) affects about 1% of working-aged people and is the commonest cause of hand pain in manual workers. CTS is a clinical diagnosis and does not warrant any further investigation in the presence of mild and suggestive CTS. Although the recommended non-surgical management is still a matter of debate, nocturnal splinting or steroid injection are recommended in most countries, with strong to moderate level of evidence for short-term efficacy. Patients with an uncertain diagnosis or severe symptoms, should undergo nerve conduction studies with referral to a hand specialist.